Fabric fiber

By thermally cracking the fabric microfibers and nanofibers and converting them into carbon nanomaterials, the problem of difficulty in converting these fibers into high-value, biodegradable products in the prior art is solved, and an efficient and environmentally friendly conversion effect is achieved.

CN119630607APending Publication Date: 2025-03-14UNIVERSITY OF SURREY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380047227.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-14
Filing Date
2023-06-13
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The prior art is difficult to effectively convert non-biodegradable fabric microfibers and nanofibers into high-value, biodegradable and environmentally friendly final products.

Method used

By thermally cracking the fabric microfibers and nanofibers under suitable conditions, it is converted to carbon nanomaterials, including using methods such as pyrolysis and hydrothermal carbonization.

Benefits of technology

The solid-to-solid conversion of fiber waste is achieved, high-value carbon products and hydrogen are produced, with minimal environmental impact and no carbon emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119630607A_ABST
    Figure CN119630607A_ABST
Patent Text Reader

Abstract

The present invention relates to the conversion of textile fibres, in particular textile microfibres and / or textile nanofibres and carbon nanomaterials thereof. The present invention extends to methods of converting non-biodegradable textile microfibers and nanofibers as well as microplastics and nanoplastics into harmless, non-toxic and / or biodegradable / biocompatible end products, and includes apparatuses and / or reactors for carrying out these methods.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to textile fibers, in particular but not limited to textile microfibers and / or textile nanofibers and their carbon nanomaterial conversion. The invention extends to methods for converting non-biodegradable textile microfibers and nanofibers and microplastics and nanoplastics into harmless, non-toxic and / or biodegradable / biocompatible end products, and includes devices and / or reactors for implementing these methods. Background Art

[0002] Fabric is a material made by weaving, knitting, felting or bonding (by mechanical, thermal or chemical treatment) linear fibers, usually for the clothing industry. The properties of a fabric depend on the type of fiber used and the treatments applied to it. There are three main types of fabrics: (i) natural fabrics, derived from renewable resources such as cotton (cellulose) and wool (protein-based); (ii) synthetic fabrics, mainly derived from non-renewable petrochemical resources such as polyester and nylon, which are one of the major contributors to micro / nanoplastic pollution; and (iii) semi-synthetic or recycled fabrics, which are produced by dissolving cellulose from wood and other sources to spin filament cellulose fibers. Depending on the production process and solvent, the last type of fabric has different names, such as rayon, lyocell, tencel, etc.

[0003] Plastics have become an increasingly important aspect of people's daily lives and activities due to their flexibility and versatility, as well as their lightness and relatively low production costs. In addition to manufacturing everyday items such as clothing and cosmetics, plastics also play a vital role in the manufacture of transportation such as cars and airplanes. In the medical field, plastic products are essential as antiseptic and disposable containers and instruments, providing the most important degree of hygiene. However, despite the value of plastics to today's consumer industries, the environmental impacts associated with post-use plastics have begun to plague human society and endanger the balance of ecosystems.

[0004] Currently, little is known about the environmental and health effects caused by plastics. Environmental issues include entrapment and destruction of wildlife habitats, ingestion hazards, and the transport of organisms to new ecosystems facilitated by plastics. Plastic pollution to which humans are exposed affects the respiratory, circulatory, and lymphatic systems and may accumulate in the liver, kidneys, and intestines. The transport and deposition of plastic particles in the human body have adverse effects on the endocrine system, most notably causing endocrine disruption. When certain polymers and their associated additives are inhaled or ingested for a long time, they may be carcinogenic and endocrine disruptors. Plastics have been shown to have reproductive effects, including breast cancer, cancer, decreased sperm count, ovarian cancer, and impaired overall fetal development; in addition, consuming plastics may lead to metabolic diseases, bladder cancer, colorectal cancer, diabetes, liver disease, etc.

[0005] In addition, most discarded plastics will eventually degrade into micro-nanoplastics under weathering and aging conditions. In recent years, people have shown increasing interest in micro-nanoplastics due to their widespread presence and their possible harmful effects on animals, humans and ecosystems. Currently, micro-nanoplastics are divided into primary and secondary micro-nanoplastics based on their sources. Due to their small size and large surface area to volume ratio, micro-nanoplastics easily absorb and accumulate pollutants and accumulate in all kinds of organisms through the digestive or respiratory systems, leading to toxicity in the food chain as a whole.

[0006] Inhalation, ingestion and skin absorption of micro-nano plastics have been identified as the three basic modes of exposure. In terms of epidemiology, respiratory-related diseases including nasal cancer, airway incarceration, respiratory diseases, cancer lung cancer and lung deposition are associated with inhaled polymer particles; micro-nano plastics ingested through food may have neurological and psychological effects; macro-sized, micro-plastics and nano-plastics used on the skin are mainly related to irritation; long-term exposure may have profound effects on these systems. However, there are still many unknowns about its effects on humans.

[0007] Micro-nano plastic pollution in the environment is divided into primary and secondary according to the source. Primary micro / nano plastics are purposefully manufactured as microscopic particles and released directly into the environment through sewage leaks or household and industrial wastewater. Primary micro-nano plastics can consist of plastic granules, pellets, powders and fibers used as personal care and cleaning product additives or industrial materials. These particles have round or amorphous shapes. For example, microbeads can come from facial scrubs, artificial microspheres are used in cosmetics and detergents, and artificial resin particles are used in industrial raw materials. Secondary micro-nano plastics are produced by the degradation of larger plastic pieces. The decomposition of these polymers is caused by ultraviolet radiation, thermal aging, biofilm growth and oxidation. Degradation is divided into photodegradation, thermal degradation, biodegradation and thermal oxidative degradation. These micro-nano plastics are mainly produced by the decomposition of plastic products widely used in packaging, construction, agriculture, transportation, fabrics and household products.

[0008] One of the main sources of micro-nanoplastics, textile fibers, should be carefully considered. Figure 1 As shown in Figure 1, they may also be referred to as microfibers or nanofibers. Washing accounts for 35% of the total micro / nanoplastics emitted to the ocean from primary sources. However, there are other fabrics that emit microplastics and nanoplastics to the air and soil, which indirectly enter the ocean and are also worth considering (see Figure 1 ). In addition, it is necessary to consider the micro- and nanofibers emitted into the air in the form of dust during clothing use, as well as particulate matter emitted by clothing dryers. These micro- and nanofibers will enter the ocean and the human respiratory system through the air.

[0009] From secondary sources, plastic products that are larger than 5 mm and enter the environment are known to degrade further and may produce micro- and nano-plastics. The same is true for fishing and aquaculture equipment, hygiene products and geotextiles. In addition, landfill of synthetic clothing is another important source of micro- and nano-fibers. The disposable and throwaway culture of fast fashion has caused a serious environmental, social and economic crisis. According to the American Apparel and Footwear Association (AAFA), more than 16 million tons of fabric waste were generated in the United States in 2015, of which only 15% was recycled, 19% was incinerated for energy recovery, and the rest (66%) was thrown into landfills. It is estimated that polymer clothing takes 200 years to degrade in landfills, and they will first fragment into micro- and nano-fibers.

[0010] Currently, methods for valorizing plastic waste include liquefaction, gasification and / or pyrolysis. Some new technologies for plastic upcycling are also being explored, such as hydrothermal carbonization, microwave-assisted conversion, plasma-assisted conversion and photoreforming.

[0011] However, there are no conversion technologies designed specifically for textile microfibers and nanofibers on the market. The main ways to mass-produce plastic waste for value are biochemical degradation and thermochemical treatment of plastics. Biochemical methods break down polymers into monomers and oligomers through enzymes, but are generally only effective for cellulose and other natural polymer products; thermochemical methods convert polymers into a product mixture consisting of gas, oil, and charcoal / tar. However, none of these methods produce high-value, biodegradable, environmentally friendly and safe products.

[0012] Therefore, there is an urgent need to provide novel and efficient methods to convert textile microfibers and nanofibers into high-value, biodegradable and / or amorphous / biocompatible and / or useful end products. Summary of the invention

[0013] Therefore, in a first aspect of the present invention, there is provided a method for converting textile microfibers and / or textile nanofibers into carbon nanomaterials, the method comprising thermally pyrolyzing the textile microfibers and / or textile nanofibers under conditions suitable for converting the textile microfibers and / or textile nanofibers into carbon nanomaterials.

[0014] Advantageously, the methods of the present invention efficiently convert textile microfibers and nanofibers into high-value carbon products (i.e., carbon nanomaterials), and in some embodiments, into one or more gases comprising primarily hydrogen, which, when used as an energy source, have minimal impact on the environment and no carbon emissions.

[0015] Surprisingly, the process of the present invention enables solid-to-solid conversion of fiber wastes and selective production of high-value products from intermediate gas or liquid phase materials. The inventors believe that this may be energy-efficient due to the micro / nanostructured nature of the starting materials. Surprisingly, it is also possible to process mixed fiber feedstocks in a reactive separation process because the properties of synthetic fibers are very different from those of natural fibers, thereby controlling the effects of different reactors on catalytic sites in mixed fiber waste feedstocks.

[0016] Preferably, the method of the present invention comprises thermal cracking of textile microfibers and / or textile nanofibers of natural, synthetic or semi-synthetic origin. The processing and treatment procedures of textiles or clothing (such as dyeing) can have a negative impact on the biodegradation of natural fibers. In addition, natural fibers are often mixed with synthetic or semi-synthetic textile fabrics, or mixed during the washing process, so the method of the present invention can be effectively applied to thermal cracking of natural textile microfibers and / or textile nanofibers. However, more preferably, the method comprises thermal cracking of synthetic or semi-synthetic textile microfibers and / or textile nanofibers. Advantageously, the method is able to use micro / nanofiber raw materials, utilize existing micro-nano structures and the clear characteristics of synthetic fibers and natural fibers to control product formation, thereby improving conversion efficiency.

[0017] The textile microfibers and / or textile nanofibers may be obtained from any of the textiles in Table 1 below:

[0018] Table 1: Textiles from which the microfibers and / or nanofibers of the present invention can be derived

[0019]

[0020] In a preferred embodiment, the textile microfibers and / or textile nanofibers may be cotton or polyethylene terephthalate (PET).

[0021] In a most preferred embodiment, the textile microfibers and / or textile nanofibers are textile waste, which may be collected from washing machine filters (referred to as "hard textile waste") and / or dryer filters (referred to as "fluffy textile waste").

[0022] The textile microfibers and / or textile nanofibers may be naturally formed, knitted, woven, felted, non-woven or bonded together, preferably mechanically, thermally or chemically treated, optionally wherein the textile microfibers and / or textile nanofibers may comprise a plastic material.

[0023] “Microfibers” and / or “nanofibers” may be used interchangeably with “microplastics” and / or “nanoplastics” and have the same meaning in the context of the present invention.

[0024] The diameter can be measured by sieving, and the diameter or length can be measured by optical measurement, such as a fiber optic quality analyzer, which optically analyzes the size (e.g., diameter and / or length) of the fiber. The average diameter or length of the textile microfibers and / or textile nanofibers can be between 0.1 μm and 5 mm, between 0.1 μm and 4 mm, between 0.1 μm and 3 mm, between 0.1 μm and 2 mm.

[0025] The average diameter or length of the textile microfibers and / or textile nanofibers may be less than 5 mm, 4 mm or 3 mm. Preferably, the diameter or length of the textile microfibers and / or textile nanofibers should be less than 2 mm or 1 mm. More preferably, the diameter or length of the textile microfibers and / or textile nanofibers should be less than 750 μm, 500 μm, 250 μm or 150 μm. Preferably, the average diameter of the textile microfibers and / or textile nanofibers is less than 100 μm, 75 μm, 50 μm or less than 35 μm.

[0026] The average diameter or length of the textile microfibers and / or textile nanofibers may be between about 0.01 and 1 mm, between about 0.01 and 0.9 mm, between about 0.01 mm and 0.8 mm, between about 0.01 mm and 0.7 mm, between about 0.01 and 0.6 mm, or between about 0.01 and 0.5 mm. The average diameter or length of the textile microfibers and / or textile nanofibers may be between about 0.02 and 1 mm, between about 0.02 and 0.75 mm, or between about 0.02 and 0.5 mm. The average diameter or length of the textile microfibers and / or textile nanofibers may be between about 0.02 and 0.9 mm, between about 0.02 and 0.8 mm, between about 0.03 and 0.7 mm, between about 0.03 and 0.6 mm, or between about 0.04 and 0.5 mm.

[0027] The average diameter or length of the textile microfibers is preferably less than 10 μm, 9 μm, 8 μm, 7 μm, 6 μm or 5 μm. The average diameter or length of the textile microfibers is preferably less than 4 μm, 3 μm, 2 μm or 1 μm.

[0028] The average diameter or length of the textile nanofibers is preferably between 1 nm and 1000 nm, between 5 nm and 900 nm, or between 10 nm and 800 nm. The average diameter or length of the textile nanofibers is preferably between 20 nm and 700 nm, between 30 nm and 600 nm, or between 50 nm and 500 nm.

[0029] The average length of the textile microfibers and / or textile nanofibers may be between 0.01 mm and 0.5 mm, between 0.02 mm and 0.3 mm, or between 0.05 mm and 0.15 mm.

[0030] The average diameter of the textile microfibers and / or textile nanofibers may be between 1 and 100 μm, between 1 and 75 μm, between 1 and 50 μm, between 1 and 40 μm, or between 6 and 36 μm.

[0031] Surprisingly, the inventors have demonstrated that recycling of textile microfibers and / or nanofibers from different sources using thermal degradation, in particular pyrolysis and hydrothermal carbonization, can produce large amounts of hydrogen (H2) and high-value nanostructured carbon. Previously, attempts to recycle mass-produced textiles were limited to thermochemical conversion of natural polymers aimed at producing gas, oil and char / tar, and upcycling of microfibers and / or nanofibers obtained from washing had not been studied. However, char / tar often contains carcinogenic polycyclic aromatic hydrocarbons (PAH) and therefore poses a considerable health threat.

[0032] Degradation can refer to the series of chemical events that lead to the breakdown of the polymer structure of the plastic, which can include solid-to-solid transformations and the formation of liquid or gaseous intermediates that subsequently react to form products. "Thermal cracking" or "cracking" refers to the process of using heat and pressure to break down large hydrocarbon molecules into smaller, lighter molecules. "Thermal cracking" or "cracking" can also refer to the process of thermally reacting inert large hydrocarbon molecules with water under specific temperature and pressure conditions to form smaller, lighter molecules.

[0033] In one embodiment, thermal decomposition of the textile microfibers and / or textile nanofibers comprises pyrolysis to achieve thermal decomposition.

[0034] Pyrolysis is a thermochemical conversion process resulting from the thermal decomposition of organic reactants under an inert atmosphere, typically used to produce liquid hydrocarbon oils, char and gases. The distribution of products is highly dependent on the reaction temperature, heating rate, duration and reactor type. Pyrolysis fluidized bed reactors are often used due to their better heat and mass transfer capabilities, resulting in increased thermal cracking and high oil yields.

[0035] Typically, the oil produced by pyrolysis can be improved into fuel for automobile engines and power plants, or used as a raw material to make valuable chemicals. Pyrolysis further produces solid products such as char. During pyrolysis and gasification, dehydration, deamination, decarboxylation and dehydrogenation of organic matter will produce aromatic char.

[0036] An industrial example is being developed by Makeen Energy, which aims to convert plastics into carbon black. Figure 2The process called "Plastcon" converts plastic waste into carbon black through pyrolysis, physically and chemically separating the plastics, followed by chemical conversion through pyrolysis. Plastcon processes mass-produced plastic waste from households and industry, and the resulting carbon black can be used to make other plastic materials. Before converting plastic waste into products that may be more harmful to the environment, it is important to consider the entire life cycle of the end product.

[0037] However, to date, there have been no successful reports of using pyrolysis to convert textile microfibers and / or nanofibers into carbon nanomaterials (such as the methods described herein). Surprisingly, the inventors observed evidence of both the original microfibers and non-fibrous nanostructures, thereby directly revealing the process of becoming a potentially useful end product through solid-to-solid conversion. Thus, the inventors have successfully optimized a pyrolysis process specifically for textile microfibers and / or nanofibers, which unexpectedly produced higher quality and quantity of carbon nanomaterials.

[0038] The pyrolysis reaction can be batch, batch-fed or continuous. The pyrolysis reaction can be carried out in one or more stage reactors, which can be fixed bed or fluidized reactors. However, preferably, the reaction is carried out in a single-stage fixed bed reactor for dry feed or in a batch hydrothermal reactor for wet feed. Compared with fluidized bed, the advantages of using fixed bed reactor include reducing energy demand, being easy to manufacture and operating.

[0039] The pyrolysis reaction may be carried out in a temperature range of 100°C to 1000°C. Preferably, the pyrolysis reaction is carried out in a temperature range of 200 to 900°C, 300 to 800°C, 400 to 700°C or 450 to 600°C. Preferably, the pyrolysis reaction is carried out in a temperature range of 460 to 550°C, 470 to 540°C, 480 to 530°C or 490 to 520°C. Preferably, the pyrolysis reaction is carried out in a temperature range of 491 to 510°C, 492 to 509°C, 493 to 508°C or 493 to 507°C. Preferably, the pyrolysis reaction is carried out in a temperature range of 494 to 506°C, 495 to 505°C, 496 to 504°C or 497 to 504°C. Preferably, the pyrolysis reaction is carried out in a temperature range between 498 to 503°C, 499 to 502°C, 499 to 501°C, or about 500°C.

[0040] Preferably, the pyrolysis reaction is carried out at a temperature below 1000°C, 900°C, 800°C, 700°C, 600°C or below 550°C. Preferably, the pyrolysis reaction is carried out at a temperature above 100°C, 200°C, 300°C, 400°C or above 450°C.

[0041] Preferably, the pyrolysis reaction is carried out at a temperature below 525°C, 500°C, 475°C, 450°C, 425°C or below 400°C. Preferably, the pyrolysis reaction is carried out at a temperature above 250°C, 275°C, 300°C, 325°C or above 350°C.

[0042] The pyrolysis reaction can be carried out under the condition that the duration is 1-200 minutes. Preferably, the duration of the pyrolysis reaction is between 1 and 175 minutes, 1 and 150 minutes, 1 and 125 minutes, 1 and 100 minutes, 1 and 75 minutes, 1 and 50 minutes or between 1 and 25 minutes. Preferably, the duration of the pyrolysis reaction is between 25 and 200 minutes, 25 and 175 minutes, 25 and 150 minutes, 25 and 125 minutes, 25 and 100 minutes, 25 and 75 minutes or between 25 and 50 minutes.

[0043] The pyrolysis reaction can be carried out in a closed environment, a vacuum environment, or in an inert gas (such as nitrogen) or carbonization (such as carbon dioxide) environment at atmospheric pressure. Preferably, the pyrolysis reaction is carried out at atmospheric pressure because it is more efficient in terms of energy consumption.

[0044] The pyrolysis reaction can be carried out with a carrier gas, which is used to maintain an inert or carburizing atmosphere during the reaction, thereby preventing the feed from burning. The carrier gas can be an inert / inert gas or carbon dioxide, or a mixture thereof. The inert / inert gas can be selected from helium, neon and argon, or a combination thereof, and other non-inert gases or carburizing gases can also be used. Preferably, the carrier gas is argon or nitrogen.

[0045] In one embodiment, the pyrolysis reaction can be carried out in the absence of a catalyst, i.e., non-catalytic pyrolysis. Alternatively, in another embodiment, the pyrolysis reaction can be carried out in the presence of a catalyst, i.e., catalytic pyrolysis. The use of a catalyst can improve the energy efficiency of thermochemical conversion, promote the concentration of the reaction and the selectivity of the product. In addition, the inventors have shown that non-biodegradable fabric microfibers and / or fabric nanofibers can be converted into amorphous carbon products that are potentially harmless to organisms using non-catalytic pyrolysis. Therefore, in embodiments in which fabric microfibers and / or fabric nanofibers are thermally cracked into carbon nanomaterials, more energy and duration are required, although the method is preferably used to convert harmful microfiber and nanofiber wastes into harmless carbon wastes.

[0046] Accordingly, in one embodiment, the pyrolysis reaction is a non-catalytic pyrolysis.

[0047] In another embodiment, the pyrolysis reaction is catalytic pyrolysis.

[0048] In embodiments where the pyrolysis is a catalytic pyrolysis reaction, the catalyst may be added to the reaction before, simultaneously with (such as mixed with) or after the textile microfibers and / or textile nanofibers begin to pyrolyze. Preferably, the catalyst is in contact with (preferably mixed with) the textile microfibers and / or textile nanofibers.

[0049] The selection of a suitable catalyst helps to influence the final structure of the carbon nanomaterial final product in the method of the present invention, the carbonization temperature and the selectivity to the desired gas or liquid phase product. Heterogeneous nickel-based catalysts are preferred because of their high catalytic activity and low cost.

[0050] In one embodiment, the catalyst may be a monometallic catalyst or a multimetallic catalyst. Preferably, the catalyst is a multimetallic catalyst. The multimetallic catalyst may be selected from Ni-Mg, Ni-Fe, Ni-Mg-Al, Ni / γ-Al2O3, Ni / α-Al2O3, Fe / γ-Al2O3, Fe / α-Al2O3 and Ni-Fe / γ-Al2O3.

[0051] However, in a preferred embodiment, the catalyst is a bimetallic catalyst Ni-Fe.

[0052] The catalyst may or may not be supported by a support composition. Preferably, however, in some embodiments, the catalyst is supported by a support composition.

[0053] The support composition can have a significant impact on the activity and stability of the catalyst. A good support composition should have a large surface area and appropriate pore size or distribution, as well as strong metal-support interaction, mechanical strength, and thermal stability. The most commonly used supports are metal oxides, zeolites, and activated carbon (AC). In addition, alumina is an excellent support material due to its strong chemical and mechanical resistance, large surface area, and specific acidic properties

[153] .

[0054] The support composition can be selected from metal oxides, zeolites, carbon and alumina. The support has a high surface area and is capable of forming multi-metal nanoparticles distributed in its pore structure. In some cases, the size of the nanoparticles will affect the final size of the carbon nanomaterial formed by the textile microfibers and nanofibers.

[0055] Catalyst systems may also need to be optimized for specific polymers. Certain compounds contained in plastic waste may hinder the catalytic thermochemical conversion process. Catalysts for thermochemical conversion of plastic waste should be resistant to air, moisture and organic contaminants and work in heterogeneous mixtures.

[0056] For supported metal catalysts, sintering of the metal is a major problem under high temperature and / or hydrothermal operating conditions, which leads to a large loss of active sites / surfaces. This is mainly caused by Ostwald ripening, metal migration and agglomeration. Therefore, preferably, the supported metal catalyst has high metal dispersion, uniform metal clusters / particle size and / or strong metal-support contact to minimize the flow and sintering of the metal. Another challenge in catalyst design is to minimize the coke formed on the active sites and to target the formation of structured carbon nanomaterials.

[0057] Catalyst composition will determine the initial relative cracking rate of polymer and the graphitization rate of deposited carbon.Catalyst composition is also very important for promoting the formation of hydrogen.As described in the embodiments, the inventors have also studied the application of hydrothermal carbonization (HTC), which is another thermal cracking method for improving fabric microfibers and nanofibers into high-value nano-carbon products and hydrogen.

[0058] Therefore, in another embodiment, the thermal decomposition of the textile microfibers and / or textile nanofibers comprises hydrothermal carbonization (HTC) to achieve the thermal decomposition.

[0059] Advantageously, the inventors surprisingly observed evidence of nanostructuring directly on solid fibers, suggesting that HTC is a promising low energy input process for making nanomaterials using waste materials that already have nanostructuring.

[0060] Hydrothermal carbonization (HTC) is a relatively new method for treating wet organic waste. HTC (also known as "wet pyrolysis") is also being considered for the stabilization of polymeric wastes such as biomass. The technology itself is a method that mimics the natural phenomenon of mineralization in aqueous media found in natural biomass.

[0061] HTC is increasingly being used in the valorization of polymer waste. Current HTC applications use various biomasses, municipal solid waste, plastics, and bulk textiles as reactants to produce solid carbon, multiple gases (such as CO2, CO, CH4, and C2H4), and petroleum products.

[0062] Traditionally, the products produced by the HTC process are usually gases (or non-condensable vapors), liquids rich in absorbent inorganics and unreacted components of the reactants, and carbon-rich solids similar to coal. Current applications of HTC use various wastes from biomass, municipal solid waste, plastics and mass-produced textiles as reactants, targeting solid carbon, different gases (such as CO2, CO, CH4 and C2H4) and petroleum products. The simulated process has successfully produced carbon-rich solids with microporous structures and nanomaterials. Further examination of the overall structure of the solids showed the presence of oxide, sulfide, and halide functional groups, depending on the raw materials used. However, to date, HTC has not successfully converted textile microfibers and / or nanofibers into high-quality carbon nanomaterials and hydrogen.

[0063] The HTC process can use a solvent to adjust the pressure in the reactor to the desired reaction conditions. In the case of water or other organic solvents, the solvent can also serve as a reactant, having a dual function. In addition, when water is used, it has an autocatalytic effect on carbonization.

[0064] Water is an excellent solvent for the hydrothermal conversion process because of its low cost, non-toxicity and abundance. In the HTC process, organic materials are hydrolyzed into low molecular weight molecules. Due to the instability and reactivity of the intermediate molecules, they will repolymerize into high molecular weight compounds.

[0065] Therefore, in a preferred embodiment, the HTC process uses water as solvent.

[0066] The HTC process can be batch, fed-batch or continuous. In the case of a batch hydrothermal reactor, the advantages of this reactor design are that the reaction is exothermic, can be carried out at lower temperatures, and can easily process wet raw materials, such as fibers collected from washing.

[0067] HTC presents a very practical and sustainable method due to the low temperatures required, the versatility of the resulting products, and its suitability for processing wet feedstocks, which is critical for the aqueous environment of micro / nanofiber waste recycling. Although HTC can be carried out at lower reaction temperatures than combustion, pyrolysis and gasification, it requires high-pressure water to achieve hydrolysis, aromatization, dehydration, recondensation and decarboxylation processes to produce high-value products. Compared to traditional liquefaction, this method does not require high-pressure H2 and uses water as a hydrogen donor for the reaction. The inventors have demonstrated that the use of textile micro / nanofibers as raw materials can increase the surface area and thus improve the efficiency of the HTC reaction. The inventors observed fiber nanostructuring (i.e., solid-to-solid conversion), which means that more energy-efficient conversions can be achieved by using micro / nanofiber waste.

[0068] The inventors conducted a temperature screening analysis of hydrothermal carbonization on real textile micro / nano plastic waste. Surprisingly, the study showed that HTC treatment of real textile micro / nano plastic waste under specific conditions can produce carbon materials such as carbon nanotubes, as well as other types of carbon materials such as graphite, graphene, carbon fiber and amorphous carbon. Advantageously, this new application of HTC converts hazardous waste into useful materials while retaining the carbon in the solid phase, thereby avoiding greenhouse gas emissions.

[0069] Furthermore, the inventors optimized the process (i.e., determined the optimal temperature and duration through experiments) in order to obtain specific products according to requirements. For example, at a temperature of around 250°C, amorphous carbon with potential biocompatibility and harmlessness is formed. However, when the temperature is increased to around 300°C, carbon fibers composed of graphite are produced.

[0070] These experiments were conducted in the absence of synthetic catalysts. However, the presence of iron and silica contamination from real washing machines on the collected microfibers indicated that autocatalytic reactions can occur. This suggests that a catalyst may not be a prerequisite, but its presence can promote and accelerate the reaction.

[0071] The inventors have successfully demonstrated that the outcome of the process can be controlled simply by adjusting the temperature and pressure. This ability to control the reaction can produce harmless carbon for disposal or valuable nanomaterials for profit. In addition, the addition of a solid catalyst can further improve the selectivity of making specific carbon nanomaterials (such as nanotubes).

[0072] Preferably, the HTC reaction may be carried out in a temperature range of 50° C. to 650° C. Preferably, the HTC reaction is carried out in a temperature range of 100 to 600° C., 150 to 550° C., 200 to 500° C., or 250 to 450° C. Preferably, the HTC reaction is carried out in a temperature range of 300 to 440° C., 320 to 430° C., 330 to 420° C., 340 to 410° C., or 350 to 400° C.

[0073] In a preferred embodiment, the HTC reaction is carried out in a temperature range between 150°C and 350°C, more preferably between 175°C and 325°C, most preferably between 195°C and 305°C.

[0074] Preferably, the HTC reaction is carried out at a temperature in the range of 150° C. to 250° C., more preferably between 175° C. to 225° C., most preferably between 190° C. to 210° C. Preferably, the HTC reaction is carried out at a temperature of about 200° C.

[0075] Preferably, the HTC reaction is carried out at a temperature in the range of 200° C. to 300° C., more preferably between 225° C. to 275° C., most preferably between 240° C. to 260° C. Preferably, the HTC reaction is carried out at a temperature of about 250° C.

[0076] Preferably, the HTC reaction is carried out at a temperature in the range of 250° C. to 350° C., more preferably between 275° C. to 325° C., most preferably between 290° C. to 310° C. Preferably, the HTC reaction is carried out at a temperature of about 300° C.

[0077] The HTC reaction can be carried out under the condition of duration between 15 minutes and 24 hours. Preferably, the duration of the HTC reaction is 30 minutes to 23 hours, 1 to 22 hours, 2 to 21 hours, 3 to 20 hours, 4 to 19 hours, 5 to 18 hours or 6 to 17 hours. Preferably, the duration of the HTC reaction is 7 to 16 hours, 8 to 16 hours, 9 to 15 hours, 10 to 14 hours, 11 to 13 hours, or about 12 hours.

[0078] In a preferred embodiment, the HTC reaction is carried out under conditions of a duration between 1 hour and 8 hours. More preferably, the HTC reaction is carried out under conditions of a duration of 1 hour, 4 hours and / or 8 hours.

[0079] The HTC reaction can be carried out under a pressure that varies according to the temperature. For example, a pressure of 22 bar can be used at 200° C., and a pressure of more than 99 bar can be used at 350° C. Therefore, in one embodiment of the invention, the HTC reaction can be carried out under a pressure of atmospheric pressure to 200 bar, or 5 bar to 200 bar. Preferably, the HTC pressure is carried out under a pressure of 15 to 150 bar, 20 to 150 bar, 30 to 150 bar or 40 to 150 bar.

[0080] HTC pressure is carried out at a pressure of 20 to 100 bar. Most preferably, HTC pressure is carried out at a pressure of 20, 40 and / or 99 bar.

[0081] In a preferred embodiment, the HTC reaction is carried out at a temperature of about 150° C. to 250° C. (preferably 200° C.) and a pressure of about 5 to 30 bar (preferably 20 bar) for a duration of at least one hour.

[0082] In a preferred embodiment, the HTC reaction is carried out at a temperature of about 200° C. to 300° C. (preferably 250° C.) and a pressure of about 30 to 50 bar (preferably 40 bar) for a duration of at least one hour.

[0083] In a preferred embodiment, the HTC reaction is carried out at a temperature of about 250° C. to 350° C. (preferably 300° C.) and a pressure of about 90 to 110 bar (preferably 99 bar) for a duration of at least one hour.

[0084] The method may include using a purge gas during the HTC process to evacuate any air that may be present in the reactor. The purge gas may be an inert gas such as nitrogen or argon.

[0085] However, in a preferred embodiment, the purge gas is nitrogen.

[0086] The HTC reaction can be carried out with or without a catalyst, i.e. using catalytic HTC or non-catalytic HTC, respectively.

[0087] Accordingly, in one embodiment, the HTC reaction may include a non-catalytic HTC reaction. The inventors have shown that non-biodegradable textile microfibers and / or textile nanofibers can be converted into amorphous / biocompatible carbon nanomaterial products using a non-catalytic HTC reaction.

[0088] Preferably, when using real textile waste as starting material, the HTC reaction is a non-catalyzed HTC reaction.

[0089] In another embodiment, the HTC reaction may be a catalytic HTC reaction.

[0090] In the embodiment where the HTC is a catalytic HTC reaction, the catalyst can be charged into the reactor before, simultaneously with (i.e., mixed with) or after the textile micro / nanofibers. Preferably, the catalyst is charged simultaneously with the textile micro / nanofibers.

[0091] The catalyst used to catalyze the HTC reaction can be as described herein for the pyrolysis reaction. Therefore, in one embodiment, the catalyst can be a monometallic or multimetallic catalyst. Preferably, the catalyst is a multimetallic catalyst. The multimetallic catalyst can be selected from Ni-Mg, Ni-Fe, Ni-Mg-Al, Ni / γ-Al2O3, Ni / α-Al2O3, Fe / γ-Al2O3, Fe / α-Al2O3 and Ni-Fe / γ-Al2O3.

[0092] However, in a preferred embodiment, the catalyst is a bimetallic catalyst Ni-Fe.The catalyst may be supported on a support composition.

[0093] like Figure 3 As shown, the pyrolysis or hydrothermal carbonization method of the present invention can produce several different products. In particular and more importantly, two key products, high-value carbon and hydrogen, are produced using the two methods described herein, which can improve the yield and quality of these final products.

[0094] Carbon nanomaterials, such as carbon nanotubes (CNTs), carbon nanofibers (CNFs), carbon nanosheets (CNSs), cup-stacked carbon nanotubes (CS-CNTs), and hollow carbon spheres (HCSs), are produced from plastic waste. However, it has been impossible to produce carbon nanomaterials from textile microfibers and nanofibers to date.

[0095] Therefore, in a preferred embodiment, the carbon nanomaterial prepared by the method of the present invention can be selected from carbon nanofibers (CNF), carbon nanosheets (CNS), carbon nanotubes (CNT), cup-stacked carbon nanotubes (CS-CNT), hollow carbon spheres (HCS), quasicrystalline carbon nanoparticles, graphite or graphene.

[0096] These carbon nanomaterials have a wide range of uses, including in batteries, solar cells, medical devices, and they may also be stored for subsequent use. Carbon nanotubes (CNTs) have attracted a lot of interest due to their thermal stability, excellent thermal and electrical conductivity, high mechanical strength, high elasticity, excellent tensile strength, flexibility, and semiconductor properties. CNTs have applications in the automotive sector, as conductive polymers, plastic reinforcement, catalytic materials, etc. In addition, CNTs are used as catalysts or catalytic supports in various important scientific fields such as energy production and storage, electronics, and medicine. Chemical vapor deposition of synthetic hydrocarbons is the most commonly used technique to produce CNTs.

[0097] Carbon nanotubes consist of a carbon-bonded material, graphene, in which carbon atoms are closely packed in an atomic-scale honeycomb (hexagonal) formation. Carbon nanotubes are cylinders made from rolled-up graphene sheets, and they offer a potentially huge source of revenue for recycling and reuse. It is envisioned that the carbon nanomaterial product of the methods described herein is used to make various types of single-walled (SWCNT), double-walled (DWCNT), and multi-walled carbon nanotubes (MWCNT).

[0098] Most established carbon nanotube synthesis methods use vacuum or hydrocarbon process gases at atmospheric pressure. However, these current methods for producing carbon nanotubes are energy intensive, environmentally unfriendly due to gas emissions, and costly. As a result, the price of the material is very high. Therefore, a more sustainable and cost-effective method for making carbon nanomaterials (CNMs) is of great commercial significance. Advantageously, the methods described herein address these issues.

[0099] In one embodiment, the method produces hydrogen gas in addition to the carbon nanomaterial.

[0100] Advantageously, hydrogen (H2) plays an important role in our current energy landscape and its use as an energy carrier will become increasingly prevalent in the future, with applications in the petrochemical industry, the semiconductor industry, as a coolant, an energy carrier, and as a rocket propellant. All thermal conversion technologies for the recycling of textile microfibers and nanofibers described here are capable of producing H2, while chemical recycling of polymers focuses solely on making hydrocarbon products. Designing selective hydrogen production processes requires the development of robust catalysts with stable activity and mechanical integrity under the various potential operating conditions and reactor geometries described above.

[0101] Currently, due to the increase in greenhouse gas emissions and the rapid increase in the use of renewable energy for electricity production in recent years, the production of green hydrogen will increase significantly in the coming decades. Hydrogen can be used as a storage medium for renewable energy, where it will be considered "green hydrogen", capable of balancing the production and demand of energy while contributing to the decarbonization of the energy system, especially in transportation and industrial heating applications.

[0102] The environmental advantages of hydrogen applications depend largely on the technology used to produce the hydrogen and its underlying source. Therefore, it is very important to establish scalable low-emission hydrogen production technologies to reduce prices and produce hydrogen on a global scale. Hydrogen is mainly produced through the low-cost / high-environmental-impact steam reforming of methane (SRM) route. Since steam reforming of methane is the most mature and cheapest industrial technology for hydrogen production, it produces most of the hydrogen. As a result, global hydrogen production emits 900 million tons of carbon dioxide per year.

[0103] Thus, the methods disclosed herein also provide a means of producing hydrogen without negatively impacting the environment. In addition, these methods simultaneously remove harmful nanoplastic waste from the environment.

[0104] Different colours are used to distinguish the various hydrogen production methods, based on the primary energy source and greenhouse gas (GHG) emission levels

[158] . Currently, the majority of hydrogen is grey hydrogen. Grey hydrogen refers to hydrogen produced by steam reforming natural gas or coal (CCUS) without capturing, using or storing the carbon. The main disadvantage of grey hydrogen is that the production of hydrogen results in large amounts of CO2 emissions, estimated at around 830 million tonnes of CO2 per year. Blue hydrogen is hydrogen produced from fossil fuels using carbon capture and storage. Currently, a hydrogen production plant only needs to install a CCUS unit to qualify as blue hydrogen. The exact amount that must be captured is not clearly defined. When applied to SRM, including post-combustion CO2 capture, the highest capture rates recorded are 90%. Blue hydrogen is now seen as a bridge technology between green hydrogen and a full transition to green hydrogen.

[0105] Green hydrogen is hydrogen made electrochemically from water using renewable energy. This type of hydrogen is particularly valuable as people move to more sustainable energy and transportation systems. While nuclear hydrogen production is not a strong advocate of hydrogen production in Europe’s hydrogen projects, it could become a viable option in other parts of the world, such as China and Russia. This is sometimes called “purple hydrogen” and is produced electrochemically using electricity from nuclear power plants.

[0106] In contrast to the conventional methods mentioned previously, turquoise hydrogen produces solid carbon as a byproduct through the pyrolysis of methane. This byproduct can be used in subsequent production processes, or can be stored more easily, thereby reducing the carbon footprint. Despite this, it has only recently sparked interest in producing hydrogen primarily through thermal decomposition. Pyrolysis has not yet become commercially competitive with steam methane reforming (SRM) in terms of hydrogen generation, but there are examples of large-scale commercial applications when the carbon product can also be sold. The hydrogen produced by the technology discussed in this application can be classified as turquoise hydrogen, which is produced by the thermal decomposition of plastics while producing low emissions. This is a way to recycle or improve recycling residues, which are currently harmful to the environment and take decades to degrade naturally. If low-emission energy sources can power the process, the carbon emissions associated with hydrogen production can be further reduced.

[0107] Thus, in one embodiment, the resulting hydrogen is turquoise hydrogen (when synthetic microfibers and / or nanofibers are used as a starting material) or green hydrogen (when natural microfibers or nanofibers are used as a starting material), or a combination thereof.

[0108] Low-carbon hydrogen production technology is essential for a decarbonized economy. Waste valorization technology should be developed in line with the hydrogen economy vision, and this invention meets these goals.

[0109] As described herein, various embodiments of the method of the first aspect convert non-biodegradable textile microfibers and / or textile nanofibers into biodegradable and / or amorphous / biocompatible carbon nanomaterial products. This is true for both pyrolysis and thermal decarbonization when used without a catalyst. Therefore, the inventors believe that they are the first to devise a method for converting non-biodegradable textiles into biodegradable and / or biocompatible waste.

[0110] Therefore, in a second aspect of the present invention, a method for converting non-biodegradable textile microfibers and / or textile nanofibers into biodegradable and / or biocompatible waste is provided, which method comprises thermally pyrolyzing the textile microfibers and / or textile nanofibers under conditions suitable for converting the textile microfibers and / or textile nanofibers into biocompatible and / or biodegradable waste.

[0111] Advantageously, the inventors have demonstrated that textile microfibers and nanofibers can be converted into solid carbon that is readily biodegradable and / or biocompatible using the methods disclosed herein in the absence of a catalyst.

[0112] Thus, in one embodiment of the method, thermal cracking of the textile microfibers and / or textile nanofibers comprises pyrolysis in order to achieve thermal cracking. Preferably, the pyrolysis is performed without any catalyst.

[0113] In another embodiment of the method, the thermal cracking of the textile microfibers and / or textile nanofibers comprises hydrothermal carbonization (HTC) in order to achieve thermal cracking. Preferably, the hydrothermal carbonization is performed without any catalyst.

[0114] Preferably, the biodegradable and / or biocompatible waste is a carbon by-product. The carbon by-product may be a solid.

[0115] When the carbon by-product is a solid carbon compound, the solid carbon by-product may be amorphous or crystalline low surface area carbon.

[0116] The non-catalytic pyrolysis and non-catalytic thermal carbonization may be performed as described herein in relation to the method of the first aspect.

[0117] In a third aspect of the present invention, there is provided an apparatus for implementing the method according to the first or second aspect.

[0118] The apparatus is preferably configured to pyrolyze textile microfibers and / or textile nanofibers under conditions suitable for converting textile microfibers and / or textile nanofibers into carbon nanomaterials.

[0119] The apparatus may include a heating furnace or a heat exchanger. The apparatus may include a reaction vessel in which the thermal cracking reaction occurs.

[0120] Thermal cracking of the textile microfibers and / or textile nanofibers may be performed by pyrolysis. In this embodiment, the apparatus preferably comprises a fixed bed continuous flow reactor, and optionally a condenser.

[0121] Thermal cracking of textile microfibers and / or textile nanofibers may be performed by hydrothermal carbonization (HTC). In this embodiment, the apparatus preferably comprises a batch reactor with temperature and pressure controllers.

[0122] All features described herein (including any accompanying claims, abstract and drawings) and / or all steps of any method or process disclosed may be combined with any aspect described above in any combination, except that some such features and / or steps are at least mutually exclusive combinations. BRIEF DESCRIPTION OF THE DRAWINGS

[0123] In order to better understand the present invention and to show how to implement the embodiments of the present invention, the present invention is exemplarily described below with reference to the accompanying drawings, in which:

[0124] Figure 1 An overview of common sources of textile microfibers and nanofibers is shown.

[0125] Figure 2 Schematic showing the conversion of plastic waste through pyrolysis, courtesy of Plastcon.

[0126] Figure 3 A schematic diagram of a first embodiment of the method of the present invention, a pyrolysis process, is shown. The method can be used with or without a catalyst. When a catalyst is used, typical end products include hydrogen and other gases, carbon nanotubes, and pyrolysis oil.

[0127] Figure 4 A schematic diagram of a second embodiment of the method of the present invention, namely a hydrothermal carbonization process, is shown. The method can also be used in the presence or absence of a catalyst.

[0128] Figure 5 An image of the fabric structure is shown.

[0129] Figure 6 The gas release behavior of textile microfibers and nanofibers during the catalytic pyrolysis of polyethylene terephthalate (PET) or polyester microfibers, nanofibers and cotton microfibers is shown in Figures A and B. The hydrogen produced during the catalytic pyrolysis of PET microfibers and nanofibers and cotton microfibers and nanofibers is shown in Figures C and D.

[0130] Figure 7 FT-IR (Fourier Transform Infrared) spectra of cotton and PET fresh / waste samples under catalytic pyrolysis are shown.

[0131] Figure 8 Shown are the thermogravimetric (TGA) and differential scanning calorimetry (DSC) curves of the combustion of samples after pyrolysis of PET (Panel A) and cotton (Panel B) in an air atmosphere (5°C / min).

[0132] Fig. 9 Raman spectra of fresh / waste cotton and PET samples under catalytic pyrolysis are shown.

[0133] Fig.10 SEM (scanning electron microscope) images of fresh cotton (A) and pyrolyzed cotton (B) are shown.

[0134] Fig.11 SEM images of fresh PET (A) and PET after pyrolysis (B) are shown.

[0135] Fig.12 The SEM-EDX (scanning electron microscopy and energy dispersive X-ray spectroscopy) elemental map of nickel, iron and carbon in the cotton pyrolysis sample is shown.

[0136] Fig.13 The SEM-EDX elemental map of Ni, Fe and C in the sample after PET pyrolysis is shown.

[0137] Fig.14 Fourier transform infrared spectra of cotton and PET samples before and after hydrothermal carbonization reaction are shown.

[0138] Fig.15 Raman spectra of fresh / reacted cotton and PET samples under catalytic hydrothermal carbonization are shown.

[0139] Fig.16 SEMs of fresh cotton (A) and cotton after HTC (B) are shown.

[0140] Fig.17 SEM images of fresh PET (A) and PET after HTC (B) are shown.

[0141] Fig.18 An image of exemplary real waste samples provided by Xeros is shown.

[0142] Fig.19 SEMs of microfiber fabric waste and products at different reaction temperatures and durations are shown. Panel A) shows an image of a fluffy sample before reaction. Panel B) shows an image of a hard sample before reaction. Panel C) shows the product obtained at 200°C for 4 hours. Panel D) shows the product obtained at 200°C for 8 hours. Panel E) shows the product obtained at 250°C for 1 hour. Panel F) shows the product obtained at 250°C for 4 hours. Panel G) shows the product obtained at 300°C for 1 hour.

[0143] Fig. 20 TEM images and EDX of the products obtained after the textile microfiber waste was reacted at 300 °C for 4 h are shown. DETAILED DESCRIPTION

[0144] The present invention relates to the direct conversion of microstructured and / or nanostructured waste fibers into microstructured and / or nanostructured carbon (possibly including solid-to-solid conversion), as well as the conversion of microfibrous and / or nanofibrous waste materials into harmless (biocompatible or biodegradable) carbon. Therefore, the inventors have developed and optimized thermal conversion methods (i.e., thermal cracking) to enable non-biodegradable textile microfibers and nanofibers to be converted into high-value and high-quality carbon nanomaterial products and hydrogen. In a first embodiment of the method, the inventors used cotton and PET microfibers and nanofibers to optimize catalytic and non-catalytic pyrolysis processes. In a second embodiment of the method, the same starting material was subsequently subjected to a hydrothermal carbonization process. Each step of these two methods has been optimized to obtain higher product yields. After testing various catalyst combinations, the inventors carefully selected the best catalyst and / or catalyst combination for the various processes discussed below.

[0145] Starting material (textile microfibers and / or nanofibers)

[0146] As a proof of concept, thermal conversion experiments were conducted using cotton (natural fiber) and polyester (synthetic fiber) as starting materials. These materials are commonly used in the textile industry. Unprocessed interlocked knitted fabrics were provided by Cotton Incorporated. The yarns contained 100% cotton and 100% polyester fibers, and the weft-knitted interlocked structure was made on a 24-needle circular knitting machine (24 needles / inch) using short-staple yarn of size 40 / 1Ne (UK cotton count, 40x 840 yards single yarn weight 1 pound).

[0147] Alternatively, real textile micro / nanofiber wastes were used. These highly heterogeneous samples were provided by Xeros. Fig.18 As shown, two different textures were identified, termed "hard" and "fluffy." The "hard" sample consisted of agglomerated fabric microfibers collected from washing machine filters and displayed a uniform color and texture; the "fluffy" sample consisted of soft fabric microfibers collected from dryer filters and had varying colors due to fabric dyeing.

[0148] Example 1: Pretreatment of starting textile material

[0149] As a pretreatment, the fabrics were washed with sodium hydroxide to remove impurities such as wax, fat, pectin, protein and organic acids from the fibers and to improve their wettability. In addition, the cotton fabrics were bleached. The fabrics were dyed in different colors (purple for cotton and pink for polyester)( Figure 5 )

[97] . The chemical elemental composition and morphological characteristics of the microfibers and nanofibers produced by fabric pretreatment are summarized in Tables 2, 3 and 4. Subsequently, the microfibers and nanofibers were used in the thermal conversion experiments discussed below.

[0150] For the real waste sample, seven different regions were identified in the "fluffy" sample, and then, in order to standardize the experiment and make the sample homogenous, equal amounts of sample were selected from each region and then ground and mixed with a headless screw. In contrast, the "hard" sample was considered homogenous, so a headless screw was used to break up agglomerates.

[0151] A mixture consisting of equal amounts of "hard" and "fluffy" samples was used for the reactions.

[0152] Table 2: Basis weight and thickness of cotton and PET fabrics

[0153]

[0154] Table 3: Average size of microfibers

[0155]

[0156] Table 4: Surface chemistry of microfibers

[0157]

[0158] Example 2: Preparation of Catalyst

[0159] Ni-Fe bimetallic catalysts were prepared in a 1:3 molar ratio and used in subsequent thermal conversion experiments. The wet impregnation synthesis method described below was chosen over other methods not only because it requires fewer preparation stages, but also because it is commonly used for supported catalysts, which usually form the active material. The metal loading was 10% by weight and the support amount was 90%, which together formed a heterogeneous catalyst.

[0160] First, the required amount of metal precursors (Ni(NO3)2·6H2O) and Fe(NO3)3·9H2O were dissolved in ethanol and added to the support γ-Al2O3. After that, in order to obtain the homogeneity of the suspension, the mixture was stirred at room temperature for 4 hours using a magnetic stirrer. Secondly, the excess ethanol was removed in a rotary evaporator under reduced pressure (50°C, 150 mmbar), and the material was dried in an oven at 80°C for 12 hours. The last step of the method was calcination at 800°C (heating rate 10°C / min) for 3 hours.

[0161] Example 3: Pyrolysis-Catalysis Method

[0162] The catalytic pyrolysis process of textile microplastics and nanoplastics is carried out in a single-stage fixed-bed reactor. The reaction system mainly consists of a quartz tube reactor with a predetermined temperature range (catalytic / non-catalytic pyrolysis interval), a gas supply system, a gas product condensation system, a gas purification system, and a gas online and offline measurement system.

[0163] Before each reaction, a quartz reactor was loaded with 30 mg of textile microfibers and / or nanofibers pre-mixed together and 15 mg of catalyst. High purity argon (99.99%) was supplied as an inert gas (110 ml / min). The pyrolysis temperature was heated from ambient temperature to 500°C, increasing by 10°C per minute. Once the temperature of 500°C was reached, the reaction was maintained at 500°C for 30 minutes. After pyrolysis, the condenser collected the condensable vapor. A small portion of the non-condensable gas was introduced into a mass spectrometer (MS) to monitor the gas changes online. According to the molecular weight of the gas, the signal was recorded and identified according to the atomic mass units of 2, 16, 26, 28, 30, 44 corresponding to the main produced gases H2, CH4, C2H2, CO+C2H4, C2H6 and CO2, respectively.

[0164] Example 3: Pyrolysis - Non-catalytic Method

[0165] The non-catalytic pyrolysis process of textile microplastics and nanoplastics was carried out as described in Example 2, but no catalyst was used in this example.

[0166] Example 4: Hydrothermal Carbonization (HTC)-Catalytic Method

[0167] The HTC reaction was carried out in a batch reactor (Parr 5500 series HPCL reactor equipped with a 4848 reactor controller) using a 300 mL PTFE gasket. 0.30 g of fabric fiber, 50 g of water and 0.15 g of catalyst were loaded into a glass-lined steel container. In order to avoid any air contamination, N2 was bubbled into the solution for 5 minutes at a stirring speed of 100 rpm before closing the reaction vessel. Then, the reactor was heated to the desired temperature (200 ° C) and maintained at a stirring speed of 300 rpm for 12 hours. The pressure of the container was fixed at 22 bar according to the natural pressure generated by the solvent (water) during the reaction. After the reaction, the spent catalyst was recovered from the liquid by filtration and then dried.

[0168] Example 5: Hydrothermal Carbonization (HTC) - Non-catalytic Method

[0169] The non-catalytic HTC process for textile microplastics and nanoplastics was performed as described in Example 4, but without using any catalyst.

[0170] Alternatively, the HTC-non-catalytic method is performed as follows.

[0171] Non-catalytic HTC reaction

[0172] The HTC reaction was carried out using a 300 mL PTFE gasket in an intermittent reactor (Parr 5500 series HPCL reactor equipped with a 4848 reactor controller). 0.30 g of fabric fiber and 50 g of water were loaded into a glass-lined steel container. In order to avoid any air contamination, N2 was bubbled into the solution for 5 minutes at a stirring speed of 100 rpm before closing the reaction vessel. Then, the reactor was heated to the desired temperature (200°C, 250°C or 300°C) and stably maintained at the temperature at a stirring speed of 300 rpm for a certain period of time (1 hour, 4 hours or 8 hours). The pressure of the container was fixed according to the natural pressure generated by the solvent (water) during the reaction. After the reaction, the post-reaction sample was recovered from the liquid by centrifugation and then dried.

[0173] After the HTC reaction was completed, the post-reaction samples were collected and then subjected to the following characterization experiments.

[0174] Elemental analysis

[0175] Elemental analysis measurements were performed using a LECO TruSpec CHNS microanalyzer (TruSpec Trace Element Series). The TruSpec Micro utilizes a combination of flowing carrier gas and a single highly selective infrared (IR) and thermal conductivity detector to simultaneously measure CHNS. 1-2 mg of sample was loaded into the sample loader. Due to the heterogeneity of the sample, multiple measurements were performed to account for errors.

[0176] Scanning electron microscopy (SEM)

[0177] The samples before and after the reaction were examined by SEM using a JEOL JSM-7100F instrument equipped with an energy dispersive X-ray spectrometer (EDS) analyzer. The samples were fixed on the sample stage using carbon paint and gold-plated to eliminate charging effects.

[0178] Transmission Electron Microscopy (TEM)

[0179] Information about the loaded metal particles was obtained by a JEOL 2100F field emission gun electron microscope operated at 200 kV and equipped with an energy dispersive X-ray detector EDX. The sample was ground into a powder and suspended in a small amount in an acetone solution using an ultrasonic bath. Some of the solution was added dropwise to a copper grid (Aname, Lacey carbon 200 mesh) and introduced into the microscope after evaporation of the solvent at room temperature. EDX-mapping analysis was performed using an INCA x-sight (Oxford Instruments) detector in STEM mode using a probe size of 1 nm.

[0180] Results and Discussion

[0181] Thermal conversion using pyrolysis

[0182] Data on the evolution and distribution of the final products were obtained using mass spectrometry analysis. Figure 6 A and 6B show the evolution of the ionic current over time during the pyrolysis catalysis of textile micro- and nanofibers using NiFe catalysts, and the real-time temperature of each experiment is plotted. Due to the very limited oxygen content of cotton and PET samples, 38.2% and 29.4%, respectively, and the presence of oxygen-containing groups within the polymer chains, it is suggested that oxygen-containing compounds, such as CO and CO2, are easily released at the beginning of the reaction. In this sense, for the signal of 28 a.u., that is, the superposition signal of C2H4 and CO, its first peak originates from the evolution of CO and the second peak is that of C2H4. It has been demonstrated that the gases produced by mass-produced plastic waste alone, through thermal cracking, are mainly composed of CH4 and C2H4; although fossil-derived CH4 and C2H4 have been reported as good carbon sources for catalytic reactions to produce CNTs, the present experiments show that the use of Ni-Fe catalysts for these carbon-forming reactions is surprisingly effective when starting from microfiber and / or nanofiber textile waste. When Ni-Fe catalysts are applied to PET and cotton textile microfibers and nanofibers, H2 is produced, with both samples reaching a maximum at 500 °C (see Figure 6 C and 6D). It should be understood that the generation of H2 has a hysteresis compared to the other gas streams generated, which may be due to the complexity of the reactions occurring, such as catalyst redox and carbon deposition.

[0183] Figure 7 Fourier transform infrared spectra of the sample and fresh / waste samples are shown. These spectra show that the heat treatment caused a clear change in chemical functionality, which changed the chemical composition of both samples and provided information about the functional groups formed on the surface of the materials, which is important for evaluating the degree of carbonization.

[0184] 3670 to 2979cm -1 The broad spectral bands between 1800 and 1900 cm may indicate the presence of surface groups such as phenol, carboxylic acid, and carboxylic acid derivatives, as well as physically adsorbed water. These bands are caused by OH stretching, but usually the OH stretching bands of carboxylic acids have strong signals in a wide spectral range. -1 The coupling bands between (C=O and COC) correspond to the symmetric and asymmetric stretching of carboxylic acids derived from anhydrides, which usually appear at 60 cm -1 In addition, 1000–1300cm -1 The nearby broad bands may be related to the CO stretching of ethers, lactones, and phenols.

[0185] TGA measurements confirmed that Figure 7 The curve in Figure 2 shows that the COR chemical functional groups are significantly reduced, which may be caused by the decomposition of ethers, lactones, phenols, etc. The reduction or disappearance of these chemical functional groups is shown in Figure 2. Figure 3 Compared to the fresh sample, the breaking of COR bonds was detected, which is a sign of carbonization process during the reaction.

[0186] Figure 8 The TGA and DSC (thermogravimetric analysis and differential scanning calorimetry) curves of the combustion (air atmosphere) of PET (Figure A) and cotton (Figure B) waste samples are shown. Clear separation marks between the two carbon types and moisture of cotton and PET raw materials are shown in the curves, namely:

[0187] 1) The amount of water present in the sample at 100°C;

[0188] 2) between 100 and 400°C, low-quality / amorphous carbon; and

[0189] 3) From 400°C to 600°C, high quality / nanostructured carbon.

[0190] From the TGA-DSC graph, combined with information related to weight loss and heat flow, the percentage of each substance in the sample can be calculated. Each positive peak in the heat flow corresponds to an exothermic reaction; due to the oxygen-containing atmosphere, this reaction is the combustion of different carbonaceous materials in the presence of oxygen. Figure 8 As shown in A, the TGA curve shows two different combustion peaks, one at 398°C can be regarded as low-quality or more amorphous carbon, and the other at 451°C can be regarded as high-quality carbon nanomaterials or more crystalline carbon. In addition, the weight percentage of each substance in the total sample was extracted, and about 70% by weight was catalyst, 9% by weight was high-quality carbon, and 17% by weight was low-quality carbon, which was produced during the pyrolysis process using polyester fabric nano / micro fibers as raw materials. Due to the presence of moisture in the sample, the remaining weight percentage in 100% can be regarded as weight loss. In summary, it can be determined from the total carbon material produced after the catalytic pyrolysis process that, using PET as raw material, about 35% is converted into high-quality carbon that can contain CNTs, and 65% is converted into low-quality carbon, which has a lower economic value but is harmless to the environment and can be used for other applications.

[0191] In addition, if Figure 8As shown in Figure B, the TGA curve exhibits two different combustion peaks, one at 381°C, which can be considered as low-quality or more amorphous carbon, and the other at 471°C, which can be considered as high-quality carbon nanomaterials or more crystalline carbon. In addition, the weight percentage of each substance in the total sample was extracted, and about 69% weight was catalyst, 16% weight was high-quality carbon, and 11% weight was low-quality carbon, which was produced during the pyrolysis process using cotton fabric nano- and microfibers as raw materials. The remaining weight percentage out of 100% can be regarded as the weight loss caused by the presence of moisture in the sample. In summary, it can be determined from the total carbon material produced after the catalytic pyrolysis process that, using cotton as raw material, about 59% was converted into high-quality carbon capable of containing carbon nanotubes, and 41% was converted into low-quality carbon.

[0192] By comparing the two total carbon conversions, it was determined that using cotton as a feedstock produced a better quality carbon than PET (59% vs. 35%). This fact could be due to the differences in the chemical structure of the two feedstocks. Cotton is a natural textile microfiber and nanofiber. This suggests that the pyrolysis process improves the quality of the carbon material, which was supported by the previous Fourier transform infrared spectroscopy analysis.

[0193] The TGA results are consistent with the Raman data obtained. Raman spectroscopy provides insight into the nature of the carbon produced during catalytic pyrolysis (see Fig. 9 ). For all waste samples, the first-order Raman spectra of cotton and PET are significantly different from those of fresh samples. Two characteristic peaks can be seen around 1350 and 1580, which are typical characteristics of sp2 bonded carbon; the Raman spectrum of disordered graphite shows two modes, G peak at 1580-16001 / cm and D peak at 1350 1 / cm, which are usually attributed to E 2g and A 1g Symmetry of phonons.

[0194] The presence of the D band indicates the presence of aromatic compounds with ring sizes greater than six fused rings. The G band is often called the "graphite band" because it involves C sp 2 Atom pair (E 2g ), while the D band is often called the “defect band” because it provides information on the morphological disorder and defects that are unique to disordered graphite (A1g).

[0195] like Fig. 9As shown, the shape and position of these bands are slightly different in different cotton and PET waste samples, indicating the presence of structural differences between the carbonaceous structures produced by catalytic pyrolysis of fresh samples. In particular, in the cotton waste samples, the D band is shifted to higher Raman shift values, while the G band is very stable at the same value in both waste samples (cotton and PET). This phenomenon indicates the nature of the carbon produced in different samples. However, the D band is a double resonance process in the Raman spectrum and is closely related to the band structure, and its position provides some information about the diameter of the carbon species. Due to the low temperature and short pyrolysis time, graphitization in these samples is negligible, as shown in the SEM photos (see Fig.10 and 11 ). As the number of defects increases, the D-band generally shifts to higher frequencies.

[0196] Although Raman spectroscopy provides valuable qualitative information, preliminary quantitative analysis can provide insights into the structural development of the produced carbonaceous materials. In this case, the D / G ratio is the semi-quantitative data derived from the Raman detection of interest. In general, the intensity ratio of these bands (D / G) is a key parameter to distinguish the types of carbon produced during thermal decomposition during catalytic pyrolysis. The conversion of nanocrystalline graphite to amorphous carbon increases the D / G ratio. The D / G ratios of cotton and PET waste samples were 0.65 and 0.75, respectively, therefore, it can be determined that the carbon prepared using cotton as a feedstock is a more crystalline and better quality carbon.

[0197] In order to study the morphological characteristics and structural changes of the prepared carbonaceous materials, SEM images were prepared. Fig.10 A shows the SEM image of a fresh cotton sample. Fig.10 B shows the SEM image of the cotton waste sample after the catalytic pyrolysis process took place. In contrast, it can be observed that the morphology of the sample changed from fibrous to round carbonaceous materials. Similarly, Fig.11 A shows the SEM image of a fresh PET sample. Fig.11 B shows the SEM image of the PET waste sample after the catalytic pyrolysis process, where the same structural changes from fibrous materials to round carbonaceous particles can be observed.

[0198] The distribution of active metal phases in the heterogeneous catalysts and the possible co-location of carbon growth during catalytic pyrolysis were investigated using energy dispersive X-ray spectroscopy (EDS) mapping analysis. Fig.12 In the figure, nickel, iron, and carbon are represented in blue, pink, and red, respectively, showing the uniform distribution of the two active phases of the catalyst when cotton is used as the raw material, and also showing the obvious carbon particles distributed on the catalyst surface. Fig.13 As shown, nickel, iron, and carbon are represented in blue, yellow, and red, respectively.

[0199] Conclusions of the pyrolysis method

[0200] After undergoing a catalytic pyrolysis process, H2 gas and two different carbonaceous materials were produced from textile microfibers and nanofibers using a bimetallic Ni-Fe catalyst. For comparison, two different types of textile microfibers and nanofibers were studied: natural cotton fibers and PET synthetic fibers. At the ideal pyrolysis temperature of 500°C, the maximum H2 production was obtained. TGA, SEM, and Raman analysis confirmed that both materials used as raw materials (cotton and PET) produced high-quality carbon. In addition, it has been demonstrated that cotton microfibers and nanofibers produce more crystalline carbon materials.

[0201] Thermal conversion using hydrothermal carbonization (HTC)

[0202] Fig.14 Fourier transform infrared spectra of the hydrothermal carbonized sample and the fresh / waste sample are shown. The spectra show that the thermal treatment leads to a significant change in the chemical functionality of both samples, thus changing the chemical composition and providing information about the functional groups formed on the surface of the material, which is crucial to determine the degree of carbonization.

[0203] This figure shows a significant reduction in the COR chemical functionality. Fig.14 The decrease or disappearance of several chemical functional groups is shown. The presence of COR bond breakage compared to the fresh sample indicates that the carbonization process occurred during the hydrothermal carbonization reaction.

[0204] Raman spectroscopy provides insight into the nature of the carbon produced during the catalytic HTC process (see Fig.15 ). For all waste samples, the first-order Raman spectra of cotton and PET are significantly different from those of fresh samples. For cotton, two characteristic peaks can be observed around 1350 and 1580 1 / cm, which are typical of sp2 bonded carbon

[102] . The Raman spectrum of disordered graphite exhibits two modes, the G peak at 1580-1600 1 / cm and the D peak at 1350 1 / cm, which are usually attributed to carbon with E 2g and A 1g Symmetry of phonons.

[0205] like Fig.15 As shown, the shapes and positions of these bands vary slightly in different cotton and PET waste samples, indicating the structural differences between the carbonaceous structures produced by HTC from fresh samples.

[0206] Although the PET waste samples clearly lack the characteristic D and G bands, indicating that reactions are occurring, some material can be burned, as shown in the TGA data, but this material is not pure carbonaceous. The materials produced from HTC using PET as feedstock can be assumed to be intermediates between the fresh samples and the carbonaceous materials. Due to the low temperatures and pressures during the HTC process, graphitization in these samples is negligible, as shown in the SEM images (see Fig.16 and 17 ).

[0207] In addition, experiments conducted on real waste samples were analyzed. In order to detect the transformation of solid materials caused by changes in temperature / pressure and process duration, the properties of the carbonaceous products formed by HTC of real textile micro / nanofibers were thoroughly examined, and the test temperatures were 200°C, 250°C and 300°C. Since the pressure is automatically generated in the batch reactor, 50 grams of water were added as the reaction medium, and the resulting pressures were about 20, 40 and 99 bar, respectively. The duration was selected to be 1h, 4h and 8h. To continue this analysis, the samples were marked according to temperature and duration, for example, the carbonaceous product obtained in the reaction under the conditions of 200°C (20 bar) and 1 hour of duration was marked as 200-1.

[0208] In this study, the inventors performed elemental analysis to investigate the composition and distribution of elements in the samples. The samples were subjected to rigorous preparation techniques, including drying, grinding and homogenization, to ensure that the analysis was representative. Elemental analysis was performed using X-ray fluorescence spectroscopy (XRF), a non-destructive analytical technique capable of determining the elemental composition of solid, powder and liquid samples. The elemental concentrations of key elements such as carbon, nitrogen, hydrogen and sulfur were determined and expressed as weight percentages, and the different values ​​are summarized in Table 4. This Table 4 shows the weight percentages of carbon (C), hydrogen (H), nitrogen (N) and sulfur (S) in the pre-reaction samples ("fluffy" and "hard") and post-reaction microfibers obtained by HTC reactions at different temperatures and durations.

[0209] Table 4 Elemental analysis results

[0210]

[0211] This elemental analysis study provided valuable insights into the elemental composition of the samples. Notably, no traces of sulfur or nitrogen were detected in any of the samples. In order to account for the high heterogeneity of the pre-reaction samples, the error percentage was calculated based on six measurements. When focusing on the carbon percentage, it can be observed that it ranges from about 43% in the pre-reaction microfibers to about 70% in the post-reaction samples at 300 °C and 4 h duration. Similarly, the percentage of hydrogen decreases with increasing temperature. These findings suggest that higher temperatures promote an increase in carbonization and dehydrogenation. Moreover, it can be concluded that the duration has little effect on the extent of carbonization.

[0212] SEM images were acquired to examine the surface morphology and microstructure of the microfibers. SEM images provide high-resolution visualization results that allow for detailed analysis of the sample’s morphology, particle size, shape, and surface features. The samples were carefully prepared by mounting them on a conductive stub and then sputter coating them with a thin layer of a conductive material such as gold. This coating helps reduce charging effects and provides enhanced conductivity during imaging. SEM images were analyzed to extract surface morphology information of the carbonaceous products obtained at different reaction temperatures and durations, such as Fig.19 shown.

[0213] It can be observed that at 200 °C, the morphology of the sample changes very little, which is consistent with the elemental analysis data in Table 4. At 250 °C, the fibers begin to disappear and amorphous carbonaceous fragments are formed. However, at 300 °C, several fibers are observed again, indicating that filamentous carbon is produced at this temperature. Therefore, it is clear that the reaction temperature "sweet spot" is between 200 °C and 300 °C.

[0214] To complete the characterization studies, transmission electron microscopy (TEM) images and energy dispersive X-ray (EDX) scanning were used to gain insight into the microstructure and composition of the microfibers. Fig. 20 As shown, after 4 hours of reaction, the production of valuable carbonaceous products was observed in the post-reaction textile microfiber waste at 300°C, i.e., several layers of graphite / graphene were found.

[0215] Conclusions of the Hydrothermal Carbonization (HTC) Method

[0216] Three different types of materials were produced from textile micro / nanofibers using a bimetallic Ni-Fe catalyst following a hydrothermal carbonization process. For comparison, two types of textile micro- and nanofibers were studied: natural cotton fibers and synthetic PET fibers. TGA, SEM, and Raman spectroscopy studies revealed that several types of amorphous carbon compounds were produced when cotton was used as a raw material; when PET was used as a raw material, the produced materials could be considered as intermediates between fresh fibers and carbonaceous materials.

[0217] Furthermore, in the absence of a catalyst, when real textile waste is used as a feedstock or starting material, different carbonaceous products can be specifically produced by adjusting the temperature during the reaction.

Claims

1. A method for converting textile microfibers and / or textile nanofibers into carbon nanomaterials, the method comprising thermally cracking the textile microfibers and / or textile nanofibers under conditions suitable for converting the textile microfibers and / or textile nanofibers into the carbon nanomaterials.

2. A method for converting non-biodegradable textile microfibers and / or textile nanofibers into biodegradable and / or biocompatible waste, the method comprising thermally cracking the textile microfibers and / or textile nanofibers under conditions suitable for converting the textile microfibers and / or textile nanofibers into biodegradable or biocompatible waste.

3. A method according to claim 1 or 2, wherein the method comprises thermal lysis of natural textile microfibers and / or nanofibers.

4. A method according to any preceding claim, wherein the method comprises thermal cleavage of synthetic or semi-synthetic textile microfibers and / or textile nanofibers.

5. The method according to any of the preceding claims, wherein the textile microfibers and / or textile nanofibers are obtained from any of the textiles in Table 1, optionally wherein the textile microfibers and / or textile nanofibers are textile waste, optionally collected as hard textile waste from a washing machine filter, and / or collected as fluffy textile waste from a dryer filter.

6. A method according to any preceding claim, wherein the textile microfibers and / or textile nanofibers are cotton or polyethylene terephthalate (PET).

7. A method according to any preceding claim, wherein the textile microfibers and / or textile nanofibers are naturally formed, knitted, woven, felted, non-woven or bonded together, optionally, mechanically, thermally or chemically treated, optionally, wherein the textile microfibers and / or textile nanofibers comprise a plastic material.

8. The method according to any of the preceding claims, wherein the average diameter or length of the textile microfibers and / or textile nanofibers is between 0.1 μm and 5 mm, between 0.1 μm and 4 mm, between 0.1 μm and 3 mm, between 0.1 mm and 2 mm.

9. The method according to any one of the preceding claims, wherein the average diameter or length of the textile microfibers and / or textile nanofibers is: (i) less than 750 μm, 500 μm, 250 μm, or less than 150 μm; and / or (ii) less than 100 μm, 75 μm, 50 μm, or less than 35 μm.

10. The method according to any of the preceding claims, wherein the average length of the textile microfibers and / or textile nanofibers is between 0.01 mm and 0.5 mm, between 0.02 mm and 0.3 mm or between 0.05 mm and 0.15 mm.

11. The method according to any of the preceding claims, wherein the average diameter of the textile microfibers and / or textile nanofibers is between 1 and 100 μm, between 1 and 75 μm, between 1 and 50 μm, between 1 and 40 μm or between 6 and 36 μm.

12. The method according to any of the preceding claims, wherein thermal cracking of the textile microfibers and / or textile nanofibers comprises pyrolysis.

13. The method of claim 12, wherein the pyrolysis reaction is batch, fed-batch or continuous.

14. The method according to claim 12 or 13, wherein the pyrolysis reaction is carried out in a single-stage or multi-stage reactor, and the reactor is a fixed bed or fluidized reactor.

15. The process according to any one of claims 12 to 14, wherein the reaction is carried out in a single-stage fixed bed reactor for dry feed, or in a batch hydrothermal reactor for wet feed.

16. The method according to any one of claims 12-15, wherein the pyrolysis reaction is carried out within the following temperature range: (i) between 100°C and 1000°C, between 200°C and 900°C, between 300°C and 800°C, between 400°C and 700°C or between 450°C and 600°C; (ii) between 460 and 550°C, between 470 and 540°C, between 480 and 530°C or between 490 and 520°C; (iii) less than 1000°C, 900°C, 800°C, 700°C, 600°C or less than 550°C; and / or (iv) greater than 100°C, 200°C, 300°C, 400°C or greater than 450°C.

17. The method according to any one of claims 12 to 16, wherein the pyrolysis reaction is carried out under the following duration conditions: (i) between 1 and 200 minutes, between 1 and 175 minutes, between 1 and 150 minutes, between 1 and 125 minutes, between 1 and 100 minutes, between 1 and 75 minutes, between 1 and 50 minutes or between 1 and 25 minutes; and / or (ii) between 25 and 200 minutes, between 25 and 175 minutes, between 25 and 150 minutes, between 25 and 125 minutes, between 25 and 100 minutes, between 25 and 75 minutes, or between 25 and 50 minutes.

18. The method according to any one of claims 12 to 17, wherein the pyrolysis reaction is carried out at atmospheric pressure.

19. The method according to any one of claims 12 to 18, wherein the pyrolysis reaction is carried out with a carrier gas, which maintains an inert or carbiding atmosphere during the reaction to prevent combustion of the feedstock, preferably, the carrier gas is argon or nitrogen.

20. The method of any one of claims 12-19, wherein the pyrolysis reaction is performed in the absence of a catalyst.

21. The method according to any one of claims 12 to 20, wherein the pyrolysis reaction is carried out in the presence of a catalyst.

22. The method of claim 21, wherein the catalyst is a monometallic catalyst or a multimetallic catalyst.

23. The method according to claim 22, wherein the multi-metal catalyst is selected from Ni-Mg, Ni-Fe, Ni-Mg-Al, Ni / γ-Al2O3, Ni / α-Al2O3, Fe / γ-Al2O3, Fe / α-Al2O3 and Ni-Fe / γ-Al2O3.

24. The method according to any one of claims 21-23, wherein the catalyst is a bimetallic catalyst Ni-Fe.

25. The method of any one of claims 21-24, wherein the catalyst is supported by a support composition, optionally wherein the support composition is selected from metal oxides, zeolites, activated carbon and alumina.

26. The method according to any one of claims 1-11, wherein the thermal cracking of the textile microfibers and / or textile nanofibers comprises hydrothermal carbonization (HTC).

27. The method according to claim 26, wherein the HTC process uses a solvent to adjust the pressure to the desired reaction conditions, preferably, wherein the solvent of the HTC is an organic compound or water.

28. The method according to claim 26 or 27, wherein the HTC reaction is carried out within the following temperature range: (i) between 50°C and 650°C, between 100°C and 600°C, between 150°C and 550°C, between 200°C and 500°C or between 250°C and 450°C; (ii) between 300 and 440°C, between 320 and 430°C, between 330 and 420°C, between 340 and 410°C or between 350 and 400°C; (iii) less than 525°C, 500°C, 475°C, 450°C, 425°C, or less than 400°C; (iv) above 250°C, 275°C, 300°C, 325°C, or above 350°C; and / or (v) between 150 and 350°C, optionally wherein the HTC reaction is carried out at a temperature of about 200°C, 250°C or 300°C.

29. The method according to any one of claims 26-28, wherein the HTC reaction is carried out under the following duration conditions: (i) between 15 minutes and 24 hours; between 30 minutes and 23 hours, 1 to 22 hours, 2 to 21 hours, 3 to 20 hours, 4 to 19 hours, 5 to 18 hours or 6 to 17 hours; (ii) between 7 and 16 hours, 8 and 16 hours, 9 and 15 hours, 10 and 14 hours, 11 and 13 hours, or about 12 hours; and / or (iii) between 1 hour and 8 hours, optionally, wherein the HTC reaction is carried out under the duration conditions of 1 hour, 4 hours or 8 hours.

30. The method according to any one of claims 26-29, wherein the HTC reaction is carried out at a pressure between normal pressure and 200 bar, between 5 bar and 200 bar, between 15 and 150 bar, between 20 and 150 bar, between 30 and 150 bar or between 40 and 150 bar, or in a pressure range of 20 to 100 bar, optionally, wherein the HTC reaction is carried out under a pressure condition of 20, 40 or 99 bar.

31. The method of any one of claims 26-30, wherein the HTC reaction comprises a non-catalytic HTC reaction or a catalytic HTC reaction.

32. The method of claim 31, wherein the catalyst is as described in any one of claims 22-25.

33. A method according to any preceding claim, wherein the carbon nanomaterial prepared by the method is selected from carbon nanofibers (CNFs), carbon nanosheets (CNS), carbon nanotubes (CNTs), cup-stacked carbon nanotubes (CS-CNTs), hollow carbon spheres (HCS), quasicrystalline carbon nanoparticles, graphite or graphene.

34. A method according to any preceding claim, wherein the method produces hydrogen in addition to producing the carbon nanomaterial.

35. An apparatus for carrying out the method according to any one of the preceding claims.

36. The apparatus of claim 35, wherein the apparatus is configured to thermally pyrolyze the textile microfibers and / or textile nanofibers under conditions suitable for converting the textile microfibers and / or textile nanofibers into carbon nanomaterials.